Pengaruh Lingkungan Kerja, Koordinasi, dan Budaya Kerja terhadap Efektivitas Kerja Pegawai di Era Pandemi - Kartika Kurniasari; Kusuma Chandra Kirana; Didik Subiyanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study was conducted to determine the effect of the work environment, coordination, and work culture on the effectiveness of employees' work in the era of the COVID-19 pandemic at the Yogyakarta Special Region of Youth and Sports Education. The method used in this study is a quantitative method with a sample of 95 respondents. Based on the multiple linear analysis method, it was found that the work environment has no significant effect on work effectiveness because the t-count value is 1.577 < 1.986, the decision shows that the work environment is not always importantto improve the quality of employee performance. Coordination has a positive effect on work effectiveness with a t value of 2.807 > 1.986. Work culture has a positive effect on the effectiveness of employees' work as evidenced by the t value of 5.988 > 1.986. Simultaneously work environment, coordination, and work culture have a significant positive effect on employee work effectiveness with Fcount of 81.861 > 0.020.